Make America Christian Again: Christian Nationalism and Voting for Donald Trump in the 2016 Presidential Election. (25th January 2018) - Whitehead, Andrew L; Perry, Samuel L; Baker, Joseph O
Abstract: Why did Americans vote for Donald Trump in the 2016 Presidential election? Social scientists have proposed a variety of explanations, including economic dissatisfaction, sexism, racism, Islamophobia, and xenophobia. The current study establishes that, independent of these influences, voting for Trump was, at least for many Americans, a symbolic defense of the United States' perceived Christian heritage. Data from a national probability sample of Americans surveyed soon after the 2016 election shows that greater adherence to Christian nationalist ideology was a robust predictor of voting for Trump, even after controlling for economic dissatisfaction, sexism, anti-black prejudice, anti-Muslim refugee attitudes, and anti-immigrant sentiment, as well as measures of religion, sociodemographics, and political identity more generally. These findings indicate that Christian nationalist ideology—although correlated with a variety of class-based, sexist, racist, and ethnocentric views—is not synonymous with, reducible to, or strictly epiphenomenal of such views. Rather, Christian nationalism operates as a unique and independent ideology that can influence political actions by calling forth a defense of mythological narratives about America's distinctively Christian heritage and future.